A multi-criteria method of compressed video sequences comparison - Pietkiewicz, Tadeusz (Видавництво Львівської політехніки, 2010)
A multi-criteria method is presented for comparison of compressed video images. As criteria are used: bit rate of video stream, subjective quality evaluation of compressed video sequence and objective quality evaluation of compressed video sequence using Average Peak Signal-to-Noise Ratio (APSNR) metric.
Keywords: video compression; multi-criteria method of